The Implications of Traditional Market Development for Governance of Conflicts: an Experience from Klewer Market of Surakarta, Indonesia - SUDARMO, SUDARMO (Universitas Muhammadiyah Yogyakarta, 2016)
Klewer market has been developing since over six decades ago. Since the beginning of its development, conflicts among stakeholders in the market have repeatedly happened. By using ethnographic method, the study shows that intensive interactions amongst the associations of traditional market traders, the City government, street traders and other interest groups of Klewer market created conflicts. The causes of conflicts are not simple. Each group of traders tends to have its own interest agenda that contradict to that of the others. In some occasions, a group of traders built social capital intended to resolve conflict but it is not always the case because it tends to be used for maximizing its own interests but at the expense of others so that vigorous conflict is unavoidable. Sometimes a conflict was managed by avoidance but it is easy to raise againsince the roots of conflict were not entirely resolved. One of the causes of conflict was the competition for limited resources among diverse interest groups. Since the city government of Surakarta has insufficient resources, it collaborated with other parties including the royal family of the former Surakarta monarchy, state banks, private enterprises and the central government to provide the required resources which is the part of governance of conflict.